Retailing strategy: The need for revision of the traditional orientation - M. Leibold (South African Journal of Business Management, 1983)
The central theme of this article is that the traditional orientation to retailing strategy seems inadequate to cope with changing environmental realities of especially the past decade. The traditional concept of retailing strategy is analysed, and the general marketing strategy nature thereof is indicated. The difference between enterprise and marketing strategy is highlighted, and the nature and importance of a broadened enterprise strategy emphasis are stressed. The latter approach incorporates three hierarchial levels of strategy orientation, which lead to appropriate decisions regarding the character, scope and mission of a retail enterprise's activities.
Keywords: 650